Physical education for children with moderate to severe disabilities - Grenier, Michelle 1956-; Lieberman, Lauren J. 1965- (Human Kinetics, 2018)
Physical Education for Children With Moderate to Severe Disabilities offers comprehensive strategies for instruction, assessment, communication, collaborative practices, peer supports, and effective use of paraeducators ; Describes unique equipment modifications and alternative programming suggestions ; Includes sample lesson plans and assessments that you can use as is or use as models to create your own ; and is applicable for children with moderate to severe disabilities in general physical education classes and self-contained PE environments. It provides all the information and guidance needed to deliver appropriate physical education to children with moderate to severe disabilities. The book will inspire you to consider the unlimited avenues for participation in sport and physical activity for all your students-even those with the most severe disabilities.